A Raspberry Pi Local Server-Based Wearable Device System for Heart Health Monitoring - Alamul iman; Juju Juhaeriyah (Jurnal Ilmiah Telsinas, 2026)
Cardiovascular diseases, including arrhythmia and heart failure, remain major causes of death worldwide. Cloud-based ECG monitoring systems may face challenges related to dependence on internet connectivity and data transmission. This study aimed to develop a prototype of a local-network-based wearable ECG monitoring system using a Raspberry Pi as a local server without relying on public internet connectivity. A modified Research and Development (R&D) method was applied through requirements analysis, system design, prototype development, and system evaluation. The system integrated an AD8232 ECG sensor, an ESP8266 microcontroller, and a Raspberry Pi. ECG data were transmitted in real time through a local Wi-Fi network using HTTP over TCP/IP and stored in a MySQL database. BPM measurements were validated against a pulse oximeter using 10 measurements for each of six participants aged 14–87 years, resulting in 60 measurements in total. The system achieved an average accuracy of 97.75% and an average error of 2.25%. The prototype successfully acquired and recorded raw ECG and BPM data, classified heart rate into predefined normal, bradycardia, and tachycardia categories, and provided corresponding LED indicators. The system is intended for ECG and heart-rate monitoring and does not provide clinical diagnosis of cardiac conditions.